Thermoplastic polyurethane with low chemical crosslinking degree and preparation method thereof

By introducing dihydroxyitocamide as a co-chain extender in TPU and combining specific ingredients and supercritical foaming technology, the shortcomings in the existing TPU materials in terms of mechanical, processing and foaming performance are solved, and high-performance sports shoe midsole material is prepared.

CN119684557AActive Publication Date: 2025-03-25LI NING (CHINA) SPORTS GOODS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411447773.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-03-25
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

Existing micro-crosslinked TPUs cannot meet the improvement of mechanical properties, processing properties and foaming properties at the same time. Especially in the application of midsole materials for sports shoes, it is difficult to achieve the requirements of lighter density, elasticity and tear resistance.

Method used

Using low-chemical cross-linking thermoplastic polyurethane, the introduction of dihydroxyitanamide as a co-chain extender, combined with specific diisocyanate, oligomer diol and cross-linking agent, TPU elastomers with low cross-linking characteristics were prepared, and shoe midsole materials were prepared through supercritical foaming technology.

Benefits of technology

The mechanical properties and foaming properties of TPU are significantly improved, and a midsole material of sports shoes with lower density, higher resilience and higher tear resistance are prepared, meeting the high requirements of modern sports shoes for material performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005088184300000021
    Figure BDA0005088184300000021
  • Figure BDA0005088184300000041
    Figure BDA0005088184300000041
  • Figure FDA0005088184290000011
    Figure FDA0005088184290000011
Patent Text Reader

Abstract

The invention provides thermoplastic polyurethane with low chemical crosslinking degree. The thermoplastic polyurethane is prepared from the following components in parts by mass: 10 to 45 parts of diisocyanate, 40 to 80 parts of oligomer dihydric alcohol, 1 to 15 parts of dihydric alcohol chain extender, 0.5 to 5 parts of dihydroxy itaconamide, 0.1 to 3 parts of crosslinking agent and 0.1 to 2 parts of thermal initiator DCP (dicumyl peroxide), dihydroxy itaconamide is used as a co-chain extender and is prepared by reacting itaconic acid or itaconate with alcohol amine. The invention also provides a preparation method of the thermoplastic polyurethane with low chemical crosslinking degree, which comprises the following steps: premixing the dihydric alcohol chain extender and the dihydroxy itaconamide, adding diisocyanate and oligomer dihydric alcohol, reacting to obtain a prepolymer, curing at 105-115 DEG C for 12-24 hours, and curing at room temperature for 7 days to obtain a TPU polymer matrix. Compared with the prior art, the preparation method has the advantages that the dihydric alcohol itaconamide is introduced into polyurethane as a co-chain extender to prepare the low-crosslinking TPU elastomer, so that the processability of the TPU elastomer is improved, the mechanical property of the TPU is also improved, and the prepared insole material is lower in density, higher in rebound resilience and higher in tear strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of foaming materials, and in particular relates to a thermoplastic polyurethane with a low chemical crosslinking degree and a preparation method thereof. Background Art

[0002] As the most basic sports equipment, the improvement and upgrade of sports shoes’ performance are the most concerned and expected by sports consumers. The wearing experience that sports shoes can provide to consumers is inseparable from the physical properties of the midsole. The performance of the midsole material directly affects the comfort and functionality of sports shoes.

[0003] Among them, thermoplastic polyurethane (TPU) is widely used in the field of sports shoes due to its excellent mechanical properties, easy processing and molding, environmentally friendly and reusable materials. TPU is a type of block copolymer composed of diisocyanate, chain extender and polyol. The hard segment composed of diisocyanate and chain extender gives the material hardness and rigidity, and the polyol soft segment makes the material flexible and tough. The regular hard segment undergoes microphase separation from the soft segment after crystallization, and the hard crystalline phase is evenly dispersed in the continuous rubber phase composed of the soft segment. Therefore, TPU exhibits the characteristics of high tensile strength, high elongation at break, and excellent rebound performance.

[0004] For example, BASF uses TPU as raw material and develops non-cross-linked TPU foamed bead material (E-TPU) through supercritical physical foaming technology, and successfully applies it to running shoe midsoles. With the continuous progress and innovation of supercritical foaming technology, TPU midsoles prepared by sheet and embryo foaming process are gradually applied to high-end shoe materials. The TPU microporous structure made by the above supercritical foaming process has low density, high specific strength, excellent rebound and shock absorption performance, and is green and environmentally friendly. It is adopted by many well-known sports shoe brands.

[0005] The basic physical properties of shoe midsoles, such as density, strength, elasticity, shock absorption and durability, are mainly determined by the molecular chain structure and molecular chain cohesion state of the materials used in the shoe midsole.

[0006] With the development of the sports shoe industry, the midsole requires lighter density, higher elasticity and tear resistance, so the strength and foaming ratio of TPU need to be further improved. Patent application CN115197392A discloses an organic peroxide micro-crosslinked modified double soft segment TPU and a preparation method, which improves the hardness and tensile strength of TPU. Patent application CN117801214A introduces hydroxyl / amine isopropylaniline chain extender crosslinking agent into TPU to improve the strength, wear resistance and heat resistance of the material. The scheme of the above patent can improve the mechanical properties of TPU to a certain extent, but does not consider the impact on the foaming performance of TPU. According to the macroscopic structural changes of TPU during supercritical foaming, in order to comprehensively improve the performance of TPU foaming materials, it is necessary not only to improve the mechanical strength of TPU itself, but also to improve its melt strength during foaming, ensure the foaming ratio, and maintain the crystallization performance and microphase separation degree of TPU after micro-crosslinking. In this way, the processability of TPU can be guaranteed and the performance of the midsole after foaming can be improved.

[0007] However, the micro-cross-linked TPU reported so far cannot meet the requirements of improving mechanical properties, processing properties and foaming properties at the same time. Summary of the invention

[0008] In view of the problem that the micro-crosslinked TPU in the prior art cannot simultaneously meet the requirements of improving mechanical properties, processing properties and foaming properties, the present invention provides a thermoplastic polyurethane with a low chemical crosslinking degree and a preparation method thereof.

[0009] The technical scheme of the present invention is as follows: a thermoplastic polyurethane with a low chemical crosslinking degree, comprising, by weight: 10 to 45 parts of diisocyanate, 40 to 80 parts of oligomer diol, 1 to 15 parts of diol chain extender, 0.5 to 5 parts of dihydroxy itaconamide, 0.1 to 3 parts of crosslinking agent, and 0.1 to 2 parts of thermal initiator DCP;

[0010] The dihydroxyitaconamide is a co-chain extender, and the general structural formula is as follows:

[0011]

[0012] Wherein n is any integer from 1 to 5.

[0013] Further, the diisocyanate includes at least one of methylene diphenyl diisocyanate, toluene diisocyanate, p-phenylene diisocyanate, xylylene diisocyanate, hexamethylene diisocyanate, methylene dicyclohexyl diisocyanate, isophorone diisocyanate, and cyclohexane dimethyl diisocyanate.

[0014] Furthermore, the diol chain extender includes at least one of ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol.

[0015] Further, the crosslinking agent includes any one of divinyl ether, ethylene glycol divinyl ether, diethylene glycol divinyl ether, polyethylene glycol divinyl ether, ethylene glycol diacrylate, butanediol diacrylate, hexanediol diacrylate, and polyethylene glycol diacrylate.

[0016] Furthermore, the molecular weight of the oligomer diol is 1,000 to 3,000.

[0017] Preferably, the diisocyanate includes at least one of methylene diphenyl diisocyanate and hexamethylene diisocyanate.

[0018] Furthermore, dihydroxyitaconamide is prepared by reacting itaconic acid or itaconic acid ester with an alcoholamine, and the alcoholamine is any one of ethanolamine, propanolamine, butanolamine, pentanolamine and hexanolamine.

[0019] Preferably, the crosslinking agent is any one of diethylene glycol divinyl ether, hexanediol diacrylate, and diethylene glycol diacrylate.

[0020] Preferably, the weight proportion of the diol chain extender is 3.5 to 4.5 parts, the weight proportion of dihydroxyitaconamide is 2 to 2.5 parts, the weight proportion of the crosslinking agent is preferably 1.5 to 2.8 parts, and the weight proportion of the thermal initiator DCP is preferably 0.8 to 1.2 parts.

[0021] The present invention also provides a method for preparing a thermoplastic polyurethane with a low chemical crosslinking degree, which is used to prepare the above-mentioned thermoplastic polyurethane with a low chemical crosslinking degree, comprising the following steps:

[0022] S1. Add diisocyanate and oligomer diol into a reaction kettle according to corresponding weight parts, add a catalyst, and heat to 80° C., stir for 2 to 3 hours under nitrogen protection, and cool to room temperature to obtain a prepolymer;

[0023] S2, vacuum degassing the prepolymer obtained in step S1 at 80° C. for 1 to 2 hours, adding a premix of a diol chain extender and dihydroxyitaconamide, stirring at high speed for 2 to 3 minutes, and then pouring into a mold, curing at 105 to 115° C. for 12 to 24 hours, and aging at room temperature for 7 days to obtain a TPU polymer matrix;

[0024] S3, the TPU polymer matrix obtained in step S1 is uniformly mixed with the crosslinking agent and the thermal initiator DCP in corresponding proportions, and granulated after twin-screw extrusion, or injection molded by a twin-screw injection molding machine to obtain a TPU elastomer with a low chemical crosslinking degree.

[0025] The advantages of the present invention are that diol itaconamide is introduced into polyurethane as a co-chain extender to produce a low-crosslinked TPU elastomer, which not only improves the processability of the TPU elastomer, but also enhances the mechanical properties of the TPU, thereby preparing a shoe midsole material with lower density, higher resilience and higher tear resistance. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] The low chemical crosslinking thermoplastic polyurethane of the present invention uses a certain amount of itaconic acid derivatives and diols as chain extenders to introduce unsaturated bonds into the side chains of TPU molecules, and then adds flexible long-chain active monomers to react with the unsaturated bonds to form TPU with a low chemical crosslinking degree. This improves the foaming performance of TPU and maintains the crystallization performance and microphase separation degree of TPU after micro-crosslinking. The itaconic acid derivatives act as co-chain extenders and play a chain extension role together with the chain extender, and are preferably in the form of dihydroxy itaconic acid amide.

[0028] Specifically, the low chemical crosslinking thermoplastic polyurethane includes, by weight: 10 to 45 parts of diisocyanate, 40 to 80 parts of oligomer diol, 1 to 15 parts of diol chain extender, 0.5 to 5 parts of dihydroxyitaconamide, 0.1 to 3 parts of crosslinking agent, and 0.1 to 2 parts of thermal initiator DCP.

[0029] The diisocyanate includes at least one of methylene diphenyl diisocyanate (MDI), toluene diisocyanate (TDI), p-phenylene diisocyanate (PPDI), xylene diisocyanate (XDI), hexamethylene diisocyanate (HDI), methylene dicyclohexyl diisocyanate (HMDI), isophorone diisocyanate (IPDI), and cyclohexane dimethyl diisocyanate.

[0030] At least one of methylene diphenyl diisocyanate (MDI) and hexamethylene diisocyanate (HDI) is preferred.

[0031] The molecular weight of the oligomer diol is 1000 to 3000, preferably 1000 to 2000, more preferably 2000; and its mass fraction is preferably 55 to 75 parts.

[0032] The diol chain extender includes at least one of ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol; the weight proportion is preferably 3.5 to 4.5 parts.

[0033] Dihydroxyitaconamide is a co-chain extender, and its general structure is as follows:

[0034]

[0035] Wherein, n=1-5, the structure is prepared by reacting itaconic acid or itaconic acid ester with an alcoholamine, wherein the alcoholamine is any one of ethanolamine, propanolamine, butanolamine, pentanolamine and hexanolamine. Preferably, the alcoholamine is any one of ethanolamine, butanolamine and hexanolamine. The mass fraction of dihydroxy itaconamide is preferably 2-2.5 parts.

[0036] The crosslinking agent includes any one of divinyl ether, ethylene glycol divinyl ether, diethylene glycol divinyl ether, polyethylene glycol divinyl ether, ethylene glycol diacrylate, butanediol diacrylate, hexanediol diacrylate, and polyethylene glycol diacrylate. Any one of diethylene glycol divinyl ether, hexanediol diacrylate, and diethylene glycol diacrylate is preferred. The crosslinking agent is preferably 1.5 to 2.8 parts by mass; the thermal initiator DCP is preferably 0.8 to 1.2 parts by mass.

[0037] The present invention also provides a method for preparing the above-mentioned thermoplastic polyurethane with low chemical crosslinking degree, comprising the following steps:

[0038] S1. Add diisocyanate and oligomer diol into a reaction kettle according to corresponding weight parts, add a catalyst, and heat to 80° C., stir for 2 to 3 hours under nitrogen protection, and cool to room temperature to obtain a prepolymer;

[0039] S2, vacuum degassing the prepolymer obtained in step S1 at 80° C. for 1 to 2 hours, adding a premix of a diol chain extender and dihydroxyitaconamide, stirring at high speed for 2 to 3 minutes, and then pouring into a mold, curing at 105 to 115° C. for 12 to 24 hours, and aging at room temperature for 7 days to obtain a TPU polymer matrix;

[0040] S3, the TPU polymer matrix obtained in step S1 is uniformly mixed with a crosslinking agent and a thermal initiator DCP in a certain proportion, and granulated after twin-screw extrusion, or injection molded by a twin-screw injection molding machine to obtain a TPU elastomer with a low chemical crosslinking degree.

[0041] The low chemical crosslinking TPU elastomer obtained by the above method has a hardness of 30-48D, preferably 40-45D, and a melting temperature of 120-180° C., preferably 120-150° C. The low chemical crosslinking TPU elastomer obtained by the present invention has a lower hardness than the common TPU elastomer (the hardness of the aliphatic TPU elastomer commonly used in the sole is mostly 85-90A, and the melting temperature is 160-190° C.), and the melting temperature range is lower and wider, which can fully fit the supercritical foaming process, and has a higher melt strength.

[0042] When the above-mentioned low chemical cross-linking TPU elastomer is used for foaming, the steps and process parameters involved in the foaming method need to fully conform to the low cross-linking structural characteristics of the thermoplastic TPU elastomer. The foaming temperature is related to the melting point of the obtained TPU elastomer. The prepared shoe midsole has light weight, high elasticity and high tear resistance.

[0043] The supercritical foaming method of thermoplastic polyurethane with low chemical crosslinking degree proposed by the present invention comprises:

[0044] S1. Weigh a low chemical crosslinking TPU elastomer, an antioxidant and a nucleating agent according to certain weight parts, place the weighed low chemical crosslinking TPU elastomer in an oven at 90-100° C. and dry for 4 hours for later use;

[0045] S2, after mixing the raw materials in step S1 evenly with a high-speed stirring device, send them into a twin-screw extruder for extrusion granulation, the particle size is controlled at 1-3mm, and the prepared pellets are stored in a dry and ventilated environment for standby use; or after mixing the raw materials evenly, send them into a twin-screw injection molding machine for injection molding, the thickness of the body is 3-10mm, and the injection-molded small embryos are stored in a dry and ventilated environment for standby use;

[0046] S3, putting the masterbatch or embryo obtained in step S2 into an autoclave, turning on the temperature controller, setting the temperature in the autoclave to 100-140°C, and after the temperature reaches the set temperature and stabilizes, introducing nitrogen or carbon dioxide into the autoclave, adjusting the gas pressure in the autoclave to 15-60MPa, and when the gas in the autoclave is in a supercritical state, maintaining constant temperature and pressure for 0.5-4 hours, and then quickly unloading the pressure to normal pressure, placing the autoclave containing the sample in ice water and cooling it to room temperature, and opening the autoclave after waiting for a certain period of time to obtain foamed beads or embryos;

[0047] S4, adding the foamed beads obtained in step S3 to a pre-opened sole mold, passing water vapor to bond and form, during which the gas pressure in the mold is maintained at 1-3 bar, the molding time is 180-300 seconds, and after demolding, drying at 50-60°C for 1-5 hours, and cooling to obtain a finished foamed midsole for sports shoes; for the foamed embryo form, placing the foamed embryo obtained in step S3 in a mold for hot pressing molding, the molding time is 180-300 seconds, and demolding after cooling to obtain a finished foamed midsole for sports shoes.

[0048] The specific properties of the thermoplastic polyurethane with low chemical crosslinking degree of the present invention are further illustrated by several groups of specific examples below.

[0049] Example 1

[0050] The low chemical crosslinking thermoplastic polyurethane includes, by mass, 25 parts of methylene diphenyl diisocyanate (MDI), 70 parts of polytetramethylene ether glycol, 4 parts of 1,4-butanediol, 2 parts of dihydroxyethyl itaconamide, 1.5 parts of crosslinking agent ethylene glycol divinyl ether, and 0.8 parts of thermal initiator DCP.

[0051] The raw materials were used according to the above preparation method to prepare a low chemical crosslinking TPU elastomer with a bulk hardness of 38D and a melting temperature of 135°C.

[0052] The low chemical crosslinking TPU elastomer is then foamed according to the above-mentioned supercritical foaming method, wherein the specific parameters of the supercritical foaming are: a twin-screw injection molding machine is used to inject into a small embryo form, the mold thickness is 5mm, the foaming agent is CO2, the foaming temperature is 137°C, the pressure in the autoclave is 25Mpa, the constant temperature and pressure are maintained for 120min, the pressure is released to normal pressure and then cooled to obtain a foamed embryo, which is hot-pressed in a sole mold into a sports shoe foam midsole test piece.

[0053] The performance test of the obtained sports shoe foam midsole test piece was carried out, and the test results were: hardness 40C, density 0.09g / cm 3 , tensile strength 3.2MPa, elongation at break 360%, energy rebound 79.5%, impact peak acceleration (PeakG) 10.27, 180 degree tear 3.3kg / cm, yellowing resistance grade 3-4.

[0054] Example 2

[0055] The low chemical crosslinking thermoplastic polyurethane includes, by mass, 35 parts of toluene diisocyanate (TDI), 60 parts of polybutylene adipate diol, 3.5 parts of 1,4-butanediol, 2 parts of dihydroxyethyl itaconamide, 1.8 parts of crosslinking agent ethylene glycol divinyl ether, and 1.0 part of thermal initiator DCP.

[0056] The raw materials were used according to the above preparation method to prepare a low chemical crosslinking TPU elastomer with a bulk hardness of 42D and a melting temperature of 137°C.

[0057] The low chemical crosslinking TPU elastomer is then foamed according to the above-mentioned supercritical foaming method, wherein the specific parameters of the supercritical foaming are: a twin-screw extruder is used to extrude beads, the beads have a particle size of 3 mm, the foaming agent is CO2, the foaming temperature is 134°C, the pressure in the autoclave is 20 MPa, the constant temperature and pressure are maintained for 90 minutes, the pressure is released to normal pressure and then cooled to obtain foamed beads, which are molded in a sole mold into a sports shoe foam midsole test piece.

[0058] The performance test of the obtained sports shoe foam midsole test piece was carried out, and the test results were: hardness 43C, density 0.07g / cm 3, tensile strength 3.6MPa, elongation at break 320%, energy rebound 82.5%, impact peak acceleration (PeakG) 11.33, 180 degree tear 3.7kg / cm, yellowing resistance grade 3-4.

[0059] Example 3

[0060] The low chemical crosslinking thermoplastic polyurethane includes, by mass, 15 parts of methylene diphenyl diisocyanate (MDI), 25 parts of hexamethylene diisocyanate (HDI), 55 parts of polytetramethylene ether glycol, 4.5 parts of 1,4-butanediol, 2.2 parts of dihydroxybutyl itaconamide, 2.5 parts of crosslinking agent diethylene glycol diacrylate, and 0.8 parts of thermal initiator DCP.

[0061] The raw materials were used according to the above preparation method to prepare a low chemical crosslinking TPU elastomer with a bulk hardness of 41D and a melting temperature of 139°C.

[0062] The low chemical crosslinking TPU elastomer is then foamed according to the above-mentioned supercritical foaming method, wherein the specific parameters of the supercritical foaming are: a twin-screw injection molding machine is used to inject into a small embryo form, the mold thickness is 5 mm, the foaming agent is CO2, the foaming temperature is 137°C, the pressure in the autoclave is 25 MPa, the constant temperature and pressure are maintained for 120 min, the pressure is released to normal pressure and then cooled to obtain a foaming mold, which is hot-pressed in a sole mold into a sports shoe foam midsole test piece.

[0063] The performance test of the obtained sports shoe foam midsole test piece was carried out, and the test results were: hardness was 41C, density was 0.06g / cm 3 , tensile strength 4.0MPa, elongation at break 290%, energy rebound 82.2%, impact peak acceleration (PeakG) 12.56, 180 degree tear 4.1kg / cm, yellowing resistance grade 3-4.

[0064] Example 4

[0065] The low chemical crosslinking thermoplastic polyurethane includes, by mass, 45 parts of hexamethylene diisocyanate (HDI), 60 parts of polytetramethylene ether glycol, 4 parts of 1,4-hexanediol, 2.5 parts of dihydroxyethyl itaconamide, 2.8 parts of crosslinking agent ethylene glycol divinyl ether, and 1.2 parts of thermal initiator DCP.

[0066] The raw materials were used according to the above preparation method to prepare a low chemical crosslinking TPU elastomer with a bulk hardness of 45D and a melting temperature of 148°C.

[0067] The low chemical crosslinking TPU elastomer is then foamed according to the above-mentioned supercritical foaming method, wherein the specific parameters of the supercritical foaming are: a twin-screw injection molding machine is used to inject into a small embryo form, the mold thickness is 8mm, the foaming agent is CO2, the foaming temperature is 145°C, the pressure in the autoclave is 35Mpa, the constant temperature and pressure are maintained for 180min, the pressure is released to normal pressure and then cooled to obtain a foamed embryo, which is hot-pressed in a sole mold into a sports shoe foam midsole test piece.

[0068] The performance test of the obtained sports shoe foam midsole test piece was carried out, and the test results were: hardness 46C, density 0.05g / cm 3 , tensile strength 4.5MPa, elongation at break 265%, energy rebound 84.6%, impact peak acceleration (PeakG) 13.27, 180 degree tear 4.5kg / cm, yellowing resistance grade 3-4.

[0069] In Examples 1-4, the specific types and weight fractions of isocyanate, oligomeric diol and dihydroxyitaconamide as co-chain extenders are different within the scope of the present invention, but it can be seen that the basic density of the low chemical crosslinking degree TPU midsole foam shoe material is less than 0.1 g / cm 3 , energy rebound is greater than 79%, and tear resistance is not less than 3.3kg / cm.

[0070] Example 5

[0071] The low chemical crosslinking thermoplastic polyurethane includes, by mass, 32 parts of hexamethylene diisocyanate (HDI), 63 parts of polybutylene adipate diol, 3 parts of 1,4-hexanediol, 2 parts of dihydroxyethyl itaconamide, 2.4 parts of crosslinking agent ethylene glycol divinyl ether, and 0.8 parts of thermal initiator DCP.

[0072] The raw materials are used to prepare a low chemical crosslinking TPU elastomer according to the above preparation method, and then the low chemical crosslinking TPU elastomer is foamed according to the above supercritical foaming method, wherein the specific parameters of the supercritical foaming are: a twin-screw injection molding machine is used to injection mold into a small embryo form, the mold thickness is 5mm, the foaming agent is CO2, and the foaming temperature is 142°C; the pressure in the autoclave is 25Mpa, the constant temperature and pressure are maintained for 120min, the pressure is released to normal pressure and then cooled to obtain a foamed embryo, which is hot-pressed in a sole mold into a sports shoe foam midsole test piece.

[0073] The performance test of the obtained sports shoe foam midsole test piece was carried out, and the test results were: hardness 46C, density 0.06g / cm 3 , energy rebound 81.6%, 180 degree tear 4.2kg / cm, yellowing resistance grade 3-4.

[0074] Example 6

[0075] The low chemical crosslinking thermoplastic polyurethane includes, by mass, 32 parts of hexamethylene diisocyanate (HDI), 63 parts of polybutylene adipate diol, 3 parts of 1,4-hexanediol, 2 parts of dihydroxybutyl itaconamide, 2.4 parts of crosslinking agent ethylene glycol divinyl ether, and 0.8 parts of thermal initiator DCP.

[0076] The raw materials are used to prepare a low chemical crosslinking TPU elastomer according to the above preparation method, and then the low chemical crosslinking TPU elastomer is foamed according to the above supercritical foaming method, wherein the specific parameters of supercritical foaming are: a twin-screw injection molding machine is used to injection mold into a small embryo form, the mold thickness is 5mm, the foaming agent is CO2, and the foaming temperature is 144°C; the pressure in the autoclave is 25Mpa, the constant temperature and pressure are maintained for 120min, the pressure is released to normal pressure and then cooled to obtain a foamed embryo, which is hot-pressed in a sole mold into a sports shoe foam midsole test piece.

[0077] The performance test of the obtained sports shoe foam midsole test piece was carried out, and the test results were: hardness 45C, density 0.07g / cm 3 , energy rebound 83.2%, 180 degree tear 3.8kg / cm, yellowing resistance grade 3-4.

[0078] Example 7

[0079] The low chemical crosslinking thermoplastic polyurethane includes, by mass, 32 parts of hexamethylene diisocyanate (HDI), 63 parts of polybutylene adipate diol, 3.5 parts of 1,4-hexanediol, 1.5 parts of dihydroxyethyl itaconamide, 2.4 parts of crosslinking agent ethylene glycol divinyl ether, and 0.8 parts of thermal initiator DCP.

[0080] The raw materials are used to prepare a low chemical crosslinking TPU elastomer according to the above-mentioned preparation method, and then the low chemical crosslinking TPU elastomer is foamed according to the above-mentioned supercritical foaming method, wherein the specific parameters of the supercritical foaming are: a twin-screw injection molding machine is used for injection molding into a small embryo form, the mold thickness is 5mm, the foaming agent is CO2, and the foaming temperature is 140°C; the pressure in the autoclave is 25Mpa, the constant temperature and pressure are maintained for 120min, the pressure is released to normal pressure and then cooled to obtain a foamed embryo body, which is hot-pressed in a sole mold into a sports shoe foam midsole test piece.

[0081] The performance test of the obtained sports shoe foam midsole test piece was carried out, and the test results were: hardness 45C, density 0.06g / cm 3 , energy rebound 81.9%, 180 degree tear 4.1kg / cm, yellowing resistance grade 3-4.

[0082] Example 8

[0083] The low chemical crosslinking thermoplastic polyurethane includes, by mass, 32 parts of hexamethylene diisocyanate (HDI), 63 parts of polybutylene adipate diol, 4 parts of 1,4-hexanediol, 1 part of dihydroxyethyl itaconamide, 2.4 parts of crosslinking agent ethylene glycol divinyl ether, and 0.8 parts of thermal initiator DCP.

[0084] The raw materials are used to prepare a low chemical crosslinking TPU elastomer according to the above preparation method, and then the low chemical crosslinking TPU elastomer is foamed according to the above supercritical foaming method, wherein the specific parameters of the supercritical foaming are: a twin-screw injection molding machine is used to injection mold into a small embryo form, the mold thickness is 5mm, the foaming agent is CO2, and the foaming temperature is 138°C; the pressure in the autoclave is 25Mpa, the constant temperature and pressure are maintained for 120min, the pressure is released to normal pressure and then cooled to obtain a foamed embryo, which is hot-pressed in a sole mold into a sports shoe foam midsole test piece.

[0085] The performance test of the obtained sports shoe foam midsole test piece was carried out, and the test results were: hardness was 44C, density was 0.08g / cm 3 , energy rebound 82.4%, 180 degree tear 3.9kg / cm, yellowing resistance grade 3-4.

[0086] Comparative Example 1

[0087] The thermoplastic polyurethane includes, by weight, 32 parts of hexamethylene diisocyanate (HDI), 63 parts of polybutylene adipate diol, and 5 parts of 1,4-hexanediol.

[0088] The raw materials are made into a TPU elastomer, and then subjected to supercritical foaming, wherein the specific parameters of the supercritical foaming are: injection molding into a small embryo form with a twin-screw injection molding machine, the mold thickness is 5 mm, the foaming agent is CO2, and the foaming temperature is 135°C; the pressure in the autoclave is 25 MPa, the constant temperature and pressure are maintained for 120 minutes, the pressure is released to normal pressure and then cooled to obtain a foamed embryo, which is hot-pressed in a sole mold into a sports shoe foam midsole test piece.

[0089] The performance test of the obtained sports shoe foam midsole test piece was carried out, and the test results were: hardness 42C, density 0.11g / cm 3 , energy rebound 76.4%, 180 degree tear 2.8kg / cm, yellowing resistance grade 3-4.

[0090] Comparative Example 2

[0091] The thermoplastic polyurethane includes, by mass, 32 parts of hexamethylene diisocyanate (HDI), 63 parts of polybutylene adipate diol, 5 parts of 1,4-hexanediol, 2.4 parts of crosslinking agent ethylene glycol divinyl ether, and 0.8 parts of thermal initiator DCP.

[0092] The raw materials are made into TPU elastomer, and then supercritical foaming is performed, wherein the specific parameters of supercritical foaming are: injection molding into a small embryo form with a twin-screw injection molding machine, the body thickness is 5mm, the foaming agent is CO2, the foaming temperature is 135°C; the pressure in the autoclave is 25Mpa, the constant temperature and pressure are maintained for 120min, the pressure is released to normal pressure and then cooled to obtain a foamed embryo, and hot pressed in a sole mold to form a sports shoe foam midsole test piece. .

[0093] The performance test of the obtained sports shoe foam midsole test piece was carried out, and the test results were: hardness 42C, density 0.11g / cm 3 , energy rebound 74.2%, 180 degree tear 3.2kg / cm, yellowing resistance grade 3-4.

[0094] In Examples 5-8, the types and mass fractions of isocyanate, oligomer diol, crosslinking agent and thermal initiator, as well as supercritical foaming conditions are fixed, and only the mass fractions of chain extender and co-chain extender are different. It can be seen that within the mass range of the present invention, the type and content of the co-chain extender have little effect on the performance difference of the final midsole product. However, in Comparative Examples 1 and 2, since the co-chain extender diol itaconamide is not introduced, the final shoe midsole performance is greatly affected, and the shoe midsole has a higher density, poorer resilience, and lower tear resistance.

[0095] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment, it is not used to limit the present invention. Any technician familiar with this patent can make some changes or modify the technical contents suggested above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the solution of the present invention.

Claims

1. A thermoplastic polyurethane with low chemical crosslinking degree, characterized in that: The composition comprises, by mass: 10 to 45 parts of diisocyanate, 40 to 80 parts of oligomer diol, 1 to 15 parts of diol chain extender, 0.5 to 5 parts of dihydroxy itaconamide, 0.1 to 3 parts of crosslinking agent, and 0.1 to 2 parts of thermal initiator DCP; The dihydroxyitaconamide is a co-chain extender, and the general structural formula is as follows: Wherein n is any integer from 1 to 5.

2. The low chemical crosslinking thermoplastic polyurethane according to claim 1, characterized in that: The diisocyanate includes at least one of methylene diphenyl diisocyanate, toluene diisocyanate, p-phenylene diisocyanate, xylylene diisocyanate, hexamethylene diisocyanate, methylene dicyclohexyl diisocyanate, isophorone diisocyanate, and cyclohexane dimethyl diisocyanate.

3. The low chemical crosslinking thermoplastic polyurethane according to claim 1, characterized in that: The diol chain extender includes at least one of ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol.

4. The low chemical crosslinking thermoplastic polyurethane according to claim 1, characterized in that: The crosslinking agent includes any one of divinyl ether, ethylene glycol divinyl ether, diethylene glycol divinyl ether, polyethylene glycol divinyl ether, ethylene glycol diacrylate, butanediol diacrylate, hexanediol diacrylate, and polyethylene glycol diacrylate.

5. The low chemical crosslinking thermoplastic polyurethane according to claim 1, characterized in that: The molecular weight of the oligomer diol is 1,000 to 3,000.

6. The low chemical crosslinking thermoplastic polyurethane according to claim 2, characterized in that: The diisocyanate includes at least one of methylene diphenyl diisocyanate and hexamethylene diisocyanate.

7. The low chemical crosslinking thermoplastic polyurethane according to claim 1, characterized in that: Dihydroxyitaconamide is prepared by reacting itaconic acid or itaconic acid ester with an alcoholamine, wherein the alcoholamine is any one of ethanolamine, propanolamine, butanolamine, pentanolamine and hexanolamine.

8. The low chemical crosslinking thermoplastic polyurethane according to claim 4, characterized in that: The crosslinking agent is any one of diethylene glycol divinyl ether, hexanediol diacrylate, and diethylene glycol diacrylate.

9. The thermoplastic polyurethane with low chemical crosslinking degree according to any one of claims 2 to 5, characterized in that: The weight of the diol chain extender is 3.5 to 4.5 parts, the weight of dihydroxyitaconamide is 2 to 2.5 parts, the weight of the crosslinking agent is preferably 1.5 to 2.8 parts, and the weight of the thermal initiator DCP is preferably 0.8 to 1.2 parts.

10. A method for preparing a thermoplastic polyurethane with a low chemical crosslinking degree, for preparing the thermoplastic polyurethane with a low chemical crosslinking degree as claimed in any one of claims 1 to 9, characterized in that: The steps include: S1. Add diisocyanate and oligomer diol into a reaction kettle according to corresponding weight parts, add a catalyst, and heat to 80° C., stir for 2 to 3 hours under nitrogen protection, and cool to room temperature to obtain a prepolymer; S2, vacuum degassing the prepolymer obtained in step S1 at 80° C. for 1 to 2 hours, adding a premix of a diol chain extender and dihydroxyitaconamide, stirring at high speed for 2 to 3 minutes, and then pouring into a mold, curing at 105 to 115° C. for 12 to 24 hours, and aging at room temperature for 7 days to obtain a TPU polymer matrix; S3, the TPU polymer matrix obtained in step S1 is uniformly mixed with the crosslinking agent and the thermal initiator DCP in corresponding proportions, and granulated after twin-screw extrusion, or injection molded by a twin-screw injection molding machine to obtain a TPU elastomer with a low chemical crosslinking degree.

Citation Information

Patent Citations

  • Organic peroxide micro-crosslinking modified thermoplastic double-soft-segment polyurethane and preparation method thereof

    CN115197392A

  • High-strength wear-resistant thermoplastic polyurethane elastomer as well as preparation method and application thereof

    CN117801214A

  • Double-bond-containing all-bio-based polyesters, and preparation method and application thereof

    CN103483571A

  • Amines having secondary aliphatic amino groups

    US20130237681A1

  • Method for synthesis and modification of bio-based polyamide

    US20220332891A1